Interactions between Vegetation and Avifauna in Amazon Forest - Dario, Fabio Rossano (Asian Journal of Biological and Life Sciences, 2013)
Vegetation is one of the most important characteristics of the environment because it supports animal life. Any interfering with the vegetation produces direct effects on the fauna through the increase, decrease, or alternation of two key attributes: food and shelter. So, the composition of life in the forest is altered as changes occur in vegetation that directly interferes with the population structure of the fauna, be those changes natural or anthropic. This fact can be realized by the alterations in the diversity and density of animal species, principally among specialist species.